2015
DOI: 10.3109/00498254.2015.1021733
|View full text |Cite|
|
Sign up to set email alerts
|

Effects ofCYP3A5genotypes,ABCB1 C3435TandG2677T/Apolymorphism on pharmacokinetics of Tacrolimus in Chinese adult liver transplant patients

Abstract: 1. The purpose of this study was to establish a population pharmacokinetic (PK) model of tacrolimus and evaluate the influence of clinical covariates, including the genetic polymorphisms of the cytochrome P450 3A5 gene (CYP3A5) and gene-encoding P-glycoprotein (ABCB1), on the PK parameters in Chinese adult liver transplant recipients. 2. Details of drug dose, sampling times and concentrations were collected retrospectively from routine therapeutic drug monitoring data early after liver transplant. Tacrolimus P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
7
35
0
1
Order By: Relevance
“…Our previous studies have demonstrated that hemoglobin, total bilirubin, and blood urea nitrogen after transplantation are significantly associated with the bioavailability of tacrolimus 14 . Clinical assessment of these liver transplant receipts revealed that the blood tacrolimus level was inversely related to the liver function evaluated by the blood levels of total bilirubin and creatinine (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous studies have demonstrated that hemoglobin, total bilirubin, and blood urea nitrogen after transplantation are significantly associated with the bioavailability of tacrolimus 14 . Clinical assessment of these liver transplant receipts revealed that the blood tacrolimus level was inversely related to the liver function evaluated by the blood levels of total bilirubin and creatinine (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that CYP3A5 genotypes affect the pharmacogenetics of tacrolimus 19, 20 because different CYP3A5 genotypes exert different characteristics of the expression of CYP3A5 14, 21 . This evidence may contribute to the interindividual variability of the tacrolimus metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] However, tacrolimus has a narrow therapeutic window and displays considerable interindividual and intra-individual variabilities in its pharmacokinetics, with poor correlation between drug dosage and blood concentrations, making it difficult to define an optimal dose schedule. 18 Currently, different tacrolimus PPK models have been set up for various populations including renal transplant patients, [19][20][21][22][23][24] liver transplant patients, [25][26][27][28][29][30] haematopoietic stem cell transplant patients 31 and lung transplant patients. Moreover, the population analysis methodology differentiates between interindividual variability and residual unexplained variability.…”
Section: What Is K Nown and Objec Tive Smentioning
confidence: 99%
“…MAP has the following advantages: patient characteristics can be incorporated into the model to improve the prediction of individualized AUC; the predictive performance can be improved with additional data; the sampling time can be chosen flexibly; and different PK parameters can be predicted simultaneously. Different TAC PPK models have been established in various populations including renal transplant patients, liver transplant patients, hematopoietic stem cell transplant patients and lung transplant patients . Some studies have tried to estimate TAC AUC using MAP.…”
Section: What Is Known and Objectivesmentioning
confidence: 99%
“…Some studies have tried to estimate TAC AUC using MAP. Some other TAC PPK studies focused on Chinese liver transplant patients . However, they only used conventional TDM data for modelling and assaying the individualized PPK parameters assay rather through Bayesian estimation.…”
Section: What Is Known and Objectivesmentioning
confidence: 99%